2011
DOI: 10.1103/physreva.84.052503
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of helium clusters with up to six atoms using soft-core potentials

Abstract: In this work we investigate small clusters of helium atoms using the hyperspherical harmonic basis. We consider systems with A = 2, 3, 4, 5, 6 atoms with an inter-particle potential which does not present a strong repulsion at short distances. We use an attractive gaussian potential that reproduces the values of the dimer binding energy, the atom-atom scattering length, and the effective range obtained with one of the widely used He-He interactions, the LM2M2 potential. In systems with more than two atoms we c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 30 publications
13
92
0
Order By: Relevance
“…[1], it has been shown that the reason for the improved convergence with increasing boson number, observed in Ref. [2], originates from the decrease of the ratio of nondiagonal coupling potential to the lowest-order diagonal potential, associated with a single Gaussian potential, as N 1/2 or faster at N → ∞. The improved convergence has been further confirmed by numerical calculations, performed with the two-body potential from Ref.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…[1], it has been shown that the reason for the improved convergence with increasing boson number, observed in Ref. [2], originates from the decrease of the ratio of nondiagonal coupling potential to the lowest-order diagonal potential, associated with a single Gaussian potential, as N 1/2 or faster at N → ∞. The improved convergence has been further confirmed by numerical calculations, performed with the two-body potential from Ref.…”
Section: Introductionsupporting
confidence: 55%
“…The convergence of the hyperspherical expansion for six atoms in Ref. [2] was better than that for four atoms both when only the two-body force was used and when the three-body force was added. This observation is important since it suggests that in the limit of a large scattering length a fast solution of the many-body problem could be achieved by using a simple phenomenological soft two-body potential plus a repulsive three-body force accounting for missing correlations between the constituents of the many-body system.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here the number in parentheses gives the difference in the last digit between the extrapolation in N and ǫ which can serve as an estimate of the numerical error. The spectra are much more compressed than the corresponding free space results [4][5][6][7][8][9]. However, a similar pattern can be observed: starting from A = 3, every A-body state is accomponied by a corresponding A + 1-body state.…”
Section: And 6 Identical Bosonsmentioning
confidence: 76%
“…In particular, there is a pair of universal four-body states associated with every Efimov state [4,5]. Moreover, universal cluster states have been predicted in five-, six-and possibly higher-body systems as well [6][7][8][9]. Using Feshbach resonances, the two-, three-, four-and five-body states have been confirmed in a ultracold atomic gases in a variety of experiments with different atom species [10][11][12].…”
Section: Introductionmentioning
confidence: 97%